Fluxes and Chern Morphisms of Hyperbolic Orbifolds - A. A. Bytsenko (Brazilian Journal of Physics, 2005)
Methods of K¡theory and spectral theory of Dirac operators are applied to describe the Chern isomorphismsand quantum fields on branes on hyperbolic manifolds.